Managing the South African Public Administration: A Complex Systems Approach - Theletsane, K. I. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
This paper aims to discuss the use of the complex systems theory in public administration. The researcher has seen in South Africa how public institutions fail to understand their role and influence in other public institutions. It is important to note that public administration is very diverse and has various stake holders and therefore, this makes it a complex environment. These stakeholders are interrelated and are part of a bigger system and with the application of systems theory the complexity will be managed. This paper is qualitative in nature and reflects elements of description. The concept of systems theory and its relationship to public administration and management practice is explored. Regarding the research methods, a literature study of appropriate primary and secondary sources containing authoritative publications, books, journals, the internet and official documents, such as departmental policies, was conducted to gather information. Towards the end of the study the researcher reflects systems theory within the South African public administration. Public Administration can be regarded as an open system, which is influenced by the environment within which it operates. The understanding of the disciplines of complexity can progress people's understanding of the complexities of public administration.
Article published in the 4th Annual International Conference on Public Administration and Development Alternative 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Complexity theory; Public administration; Reductionism systems theory; Systems thinking; Public administration